2017
DOI: 10.1088/1361-6501/aa8545
|View full text |Cite
|
Sign up to set email alerts
|

Optimal arrangements of scanning heads for self-calibration of angle encoders

Abstract: The calibration of the angle encoder is necessary to improve the accuracy of angle measurement in precision rotating devices. Due to the characteristics of in situ calibration of encoders, self-calibration methods depending on special arrangements of multiple scanning heads have been widely used. Conventional works usually arrange the scanning heads in a regularly distributed way, generally involving too many scanning heads, especially when more high order Fourier components of the encoder error are calibrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…First, the compensation model of angle measurement error at each specific temperature is built by using Fourier expansion, as shown in Equation (13). Then the relationship between the coefficients of the Fourier series and ambient temperature is established by using of polynomial fitting separately, as shown in Equation (14). The orders of Fourier series are from 0 to 7, the degree of polynomial is 5.…”
Section: Fepf Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the compensation model of angle measurement error at each specific temperature is built by using Fourier expansion, as shown in Equation (13). Then the relationship between the coefficients of the Fourier series and ambient temperature is established by using of polynomial fitting separately, as shown in Equation (14). The orders of Fourier series are from 0 to 7, the degree of polynomial is 5.…”
Section: Fepf Methodsmentioning
confidence: 99%
“…The angle measurement error was decreased significantly [11][12][13]. The multi-reading heads were set in an irregularly distributed way and the transfer function was used to realize self-calibration of rotary encoder installed in the precise rotary table [14,15]. The researches mentioned above proposed many methods to correct the angle measurement error of the rotary encoder effectively without considering the effect of the ambient temperature.…”
Section: Introductionmentioning
confidence: 99%
“…(a) Most researchers have focused on the circular grating's accuracy of ground systems such as the articulated arm coordinate measuring machine (AACMM) and telescope control system. (b) Many scholars studied the compensation methods and self-calibration [27,28] of circular grating by multi reading heads. However, few research studies concerning the algorithm compensation can be found in recent years, and the comparison of the algorithm and hardware method has not been the focus of research on compensation of the circular grating.…”
Section: Introductionmentioning
confidence: 99%
“…The rotary table has been widely used in many areas such as synthetic aperture radar System (SAR) [1], industrial applications [2][3] [4][5] [6], calibration tools [7][8] [9], transportation systems [10] and so on. In order to get a satisfactory result, the rotary table has to meet high precision output which in this case is an accurate position of determined angle.…”
Section: Introductionmentioning
confidence: 99%